Implementasi Metode Iqro Dalam Meningkatkan Kemampuan Membaca Al-Qur'an di TPQ At-Tadris Kampung Tanah Koja Jakarta Barat - Irna Awliyah; Muhammad Abdullah Darras (Jurnal Kewarganegaraan, 2024)
Abstract This research aims (1) To implement the Iqra method in improving the ability to read the Al-Qur'an at TPQ At-Tadris Kampung Tanah Koja, West Jakarta. (2) To determine the supporting and inhibiting factors of the Iqra method in improving the ability to read the Al-Qur'an at TPQ At-Tadris Kampung Tanah Koja, West Jakarta. This research uses qualitative methodology. The research participants were teaching staff at TPQ At-Tadris. The data collection method is through the process of observing, conducting interviews, and documenting information. Researchers found that the implementation of the Iqra Methodology was effective in increasing proficiency in reading the Al-Quran. This method contains four main components: initial, core, closing activities, and assessment of the learning process. 2) Supporting factors in increasing the ability to read the Al-Qur'an through iqro are cultivating the habit of studying diligently among students, providing students with their own iqro books to increase their learning motivation, and having sincere intentions from the teacher. The presence of complete educational facilities greatly facilitates the process of learning the Koran. Without adequate facilities, the learning process will inevitably be hampered. Meanwhile, the inhibiting factor is that the influence of the environment and family is an obstacle. It is important for families, especially parents, to play an active role in developing the character of students. Consequently, students will improve their understanding of the teachings presented in TPQ by reviewing similar topics at home. As a result, the function of the family is very important, especially in reading the Koran. And there are still students who continue to chat, joke and walk around during the lesson, showing a lack of discipline among the students. Keywords: Implementation, Iqro Method, Ability to Read Al-Quran, TPQ   Abstrak Penelitian ini bertujuan (1) Untuk mengimplementasikan metode Iqra dalam meningkatkan kemampuan membaca  Al-Qur’an di TPQ At-Tadris Kampung Tanah Koja, Jakarta Barat. (2) Untuk mengetahui faktor pendukung dan penghambat metode Iqra dalam meningkatkan kemampuan membaca Al-Qur'an di TPQ At-Tadris Kampung Tanah Koja Jakarta Barat. Riset ini memakai metodologi kualitatif. Peserta riset ialah tenaga pendidik di TPQ At-Tadris. Metode pengambilan data melalui proses observasi, melakukan wawancara, dan mendokumentasikan informasi. Peneliti menemukan bahwa implementasi Metodologi Iqra efektif meningkatkan kemahiran membaca Al-Quran. Metode ini memuat empat komponen utama: kegiatan awal, inti, penutup, dan penilaian proses pembelajaran. 2) Faktor yang mendukung dalam peningkatan kemampuan membaca Al-Qur’an lewat iqro ialah dengan menumbuhkan kebiasaan rajin belajar di kalangan santri, membekali santri dengan buku iqro sendiri untuk meningkatkan motivasi belajarnya, dan adanya niat yang tulus dari guru. Kehadiran fasilitas pendidikan yang lengkap sangat memudahkan proses pembelajaran Al-Qur'an. Tanpa adanya fasilitas yang memadai mau tidak mau proses pembelajaran menjadi terhambat. Sedangkan faktor penghambatnya adalah adanya pengaruh lingkungan dan keluarga menjadi kendala. Pentingnya bagi keluarga, khususnya orang tua, untuk berperan aktif dalam pengembangan karakter santri. Konsekuensinya, murid akan meningkatkan pemahamannya terhadap ajaran yang disampaikan di TPQ dengan mereview topik yang serupa di rumah. Alhasil, fungsi keluarga begitu penting, terutama dalam membaca Al-Qur’an. Dan masih ada santri yang terus mengobrol, bercanda, dan berjalan-jalan selama pembelajaran berlangsung, menunjukkan kurangnya  ke disiplinan pada santri. Kata Kunci: Implementasi, Metode Iqro, Kemampuan Membaca Al-Quran, TPQ